Prof. Mohammad Al-Drubi's Manuscripts Editing Methodology (Journal of the College of Education for Women, 2019)
Efforts of evaluating manuscripts have developed into sciences that take interest into the development of authorship movement. Expanding the rules and fundamentals of this scientific process along with the growing use of modern methods and techniques contributed further to its development.Such a disciplinedemands comprehensive knowledge in various fields to reach the most valid results that help reveal significant aspects of the cultural heritage since such a process is an ethical responsibility .Therefore, the editor has to be patient and honest in correcting mistakes, choosing the most acceptable narration and pinpointing the additions and differences as well as other requirements of serious editing.The study was divided into an entrance where it stopped at the investigator's life and achieved the books and letters. Then came the first demand to stand in the letters and the books to present the nature and subjects. Then came the second demand to stop the features of the investigation method at the Drubi and its milestones